2013
DOI: 10.1021/ef302036s
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Parameters for the Simulation of Foam Flow through Porous Media. Part 1: The Dry-Out Effect

Abstract: We develop a method of estimating foam simulation parameters from laboratory experiments. Gas and surfactant solution are coinjected into sand packs at different experimental conditions in two systems. At steady state, saturation of the aqueous phase is shown to be relatively constant over a wide range of foam qualities. In order to obtain an accurate model fit at the transition foam quality, the difference between the foam model parameter fmdry and the transition water saturation S w t is identified and a met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
131
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(135 citation statements)
references
References 70 publications
4
131
0
Order By: Relevance
“…These parameters are presented in Table 4. In addition, using the data reported by Ma et al (2013), who studied the effect of surfactant concentration on foam in sandpacks, we find a trend of increasing P c * with increasing surfactant concentration ( Table 5). The smaller values of the P c * values in Table 5 compared to those reported in Figure 7 are due to very high permeability of the rock used by Ma et al experiments.…”
Section: Effect Of Properties Of Surfactant Solution On Limiting Capisupporting
confidence: 65%
See 3 more Smart Citations
“…These parameters are presented in Table 4. In addition, using the data reported by Ma et al (2013), who studied the effect of surfactant concentration on foam in sandpacks, we find a trend of increasing P c * with increasing surfactant concentration ( Table 5). The smaller values of the P c * values in Table 5 compared to those reported in Figure 7 are due to very high permeability of the rock used by Ma et al experiments.…”
Section: Effect Of Properties Of Surfactant Solution On Limiting Capisupporting
confidence: 65%
“…We focus our study on one steady-state implicit-texture foam model, that in STARS (Computer Modeling Group, 2012;Farajzadeh et al, 2012;Ma et al, 2013Ma et al, , 2014. In that model gas mobility is scaled by a function, FM, when foam is present:…”
Section: Implicit-texture Foam Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we chose 100 for fmmob, which is less than these employed by earlier researchers, such as 1000 (Rossen et al 2006), 3000 (Rossen and Shen 2007;Jamshidnezhad et al 2008a), or 5000 (Cheng et al 2000;Rossen and Renkema 2007;Kloet et al 2009), because we believe too strong foam used previously masked some details in the foam process, which is crucial for the novel foam. Meanwhile, it is also much less than the result of coreflood matching (Ma et al 2013) because the foam in 3D is much weaker than in 1D, which has been demonstrated by Li et al (2006). In simulations, we made fmsurf equal to the injected surfactant concentration (3.34 9 10 -5 , molar fraction) (Hanssen et al 1994;Rossen and Renkema 2007).…”
Section: Reservoir Modelmentioning
confidence: 99%